2014
DOI: 10.1126/scisignal.2005413
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial regulation of epsin abundance and VEGFR3 signaling are required for lymphatic valve formation and function

Abstract: Lymphatic valves prevent the backflow of the lymph fluid and ensure proper lymphatic drainage throughout the body. Local accumulation of lymphatic fluid in tissues, a condition called lymphedema, is common in individuals with malformed lymphatic valves. The vascular endothelial growth factor receptor 3 (VEGFR3) is required for the development of lymphatic vascular system. The abundance of VEGFR3 in collecting lymphatic trunks is high before valve formation and, except at valve regions, decreases after valve fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 56 publications
2
64
0
Order By: Relevance
“…Loss of Epsins resulted in the maintenance of high Vegfr3 expression in collecting lymphatic vessels, which blocked their maturation and the formation of the valves, which caused defective lymphatic drainage. Interestingly, decreased activity of Vegfr3 in these mice restored normal lymphatic valve formation and improved lymphatic function (617). This study indeed revealed that the posttranscriptional modification of the lymphatic genes affects lymphatic valve development.…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Epsins resulted in the maintenance of high Vegfr3 expression in collecting lymphatic vessels, which blocked their maturation and the formation of the valves, which caused defective lymphatic drainage. Interestingly, decreased activity of Vegfr3 in these mice restored normal lymphatic valve formation and improved lymphatic function (617). This study indeed revealed that the posttranscriptional modification of the lymphatic genes affects lymphatic valve development.…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…In the case of Milroy disease, caused by mutations of either VEGFR3 or its agonist VEGF-C (131, 328, 384, 516), both impaired fluid absorption in the initial lymphatics was initially proposed as a disease mechanism (684). However, more recent findings that VEGFR3 contributes to lymphatic valve formation and function suggest that valve dysfunction may also be a critical factor (617). In lymphedema distichiasis syndrome, caused by mutation of FOXC2 (317), patients present with aberrant eyelashes at birth, but the onset of lymphedema typically occurs at puberty or later in life, sometimes as late as over 50 years of age (132).…”
Section: Lymphedemamentioning
confidence: 99%
“…Besides blood vessels, the lymphatic route provides an important, yet under-appreciated role for facilitating tumor development and progression. The finding that temporal and spatial regulation of epsin abundance, as well as the VEGFR3 signaling required for lymphatic valve formation and function, provides a hint that epsins may also affect tumor-associated lymphangiogenesis [53]. The increasing understanding of additional extrinsic roles of epsins will further contribute together in maximizing tumor inhibition.…”
Section: Perspectivesmentioning
confidence: 99%
“…Selectivity towards ubiquitinated proteins is mediated by two evolutionarily conserved ubiquitin interacting motifs (UIMs) located between the membrane-localizing epsin NH 2 -terminal homology (ENTH) domain and carboxyl-terminal clathrin- and AP-2 binding motifs 9, 16, 17, 19, 23, 25, 26 . Mammals express three epsins: epsins 1 and 2, which are ubiquitously expressed and redundant in function, and epsin 3, which is expressed primarily in the stomach and epidermis 9, 10, 14, 19, 27-30 . Germ line epsins 1 and 2 double knockout (DKO) mice exhibit severe vascular defects resulting in embryonic lethality 10, 27 .…”
Section: Introductionmentioning
confidence: 99%